MARKETING MIX STRATEGY OF TOFU PRODUCTS IN TOFU AGROINDUSTRY IN JAMBI CITY - Almira, Inez; Fitri, Yanuar; Effran, Endy (JALOW | Journal of Agribusiness and Local Wisdom, 2023)
This research aims to (1) Describe the general picture of the tofu agroindustry in Jambi City, (2) Analyze aspects of the marketing mix that has been implemented by the tofu agroindustry in Jambi City. The selection of the research location was carried out purposively by considering production capacity and number of workers. Respondents in this research are agro-industry owners. The analytical method used is descriptive qualitative by providing assessments using a Likert scale (4,3,2,1). The results of this research show that, (1) the Tofu Koni, Tagor Kuring, and Ghaizan Alfarizi agro-industry is an industry that produces wet tofu and dry tofu located in Jambi City with different numbers of workers, namely 9 people, 6 people, and 3 people. . Production activities are carried out every day and use grinding machine technology. Products are distributed to market distributors in Jambi City. The selling price of the product is different for each agro-industry starting from Rp. 600 – Rp. 11,000, (2) The overall implementation of the 7P marketing mix strategy implemented by Tahu Koni Agroindustry, Tagor Kuring Agroindustry, and Ghaizan Alfarizi Agroindustry is in the good category. The three agro-industries can maintain aspects of the marketing mix that are in the good category and improve and improve aspects of the marketing mix that are still in the poor category. Aspects that need to be improved are the promotion aspect, the people aspect and the physical evidence aspect.